Risk of malignancy in adrenal tumors in patients with a history of cancer - Samsel, Radosław; Nowak, Karolina; Papierska, Lucyna; Karpeta, Edyta; Roszkowska-Purska, Katarzyna; Smiertka, Wacław; Ostrowski, Tomasz; Chrapowicki, Eryk; Grabowski, Alan; Leszczyńska, Dorota; Cichocki, Andrzej (Frontiers in Oncology, 2023)
Purpose Adrenal gland is a common site of metastasis and on the other hand, metastases are the most frequent malignant adrenal tumors. The aim of this study was to estimate the risk of malignancy in indeterminate adrenal mass in patients with a history of cancer. Methods This is a single-center retrospective analysis of patients with adrenal tumors treated previously for different types of cancers. Between 2004 and 2021 a hundred and six such patients were identified. Mean age of patients was 62.6 years (30-78), and mean time from oncologic treatment was 55.8 months (0-274). The most common primary cancer was kidney (RCC): 29 (27.4%), colon/rectum (CRC): 20 (18.9%) and lung (NSCLC): 20 (18.9%). Results Of 106 patients, 12 had hormonally active (HA) (11,3%) and 94 (88,7%) non active (HNA) tumors. Primary (PM) and secondary (SM) malignancies were found in 50 patients (47.2%). In hormone inactive group only SM - 46/94 (48.9%) were diagnosed. The odds that adrenal lesion was a metastasis were higher if primary cancer was RCC (OR 4.29) and NSCLC (OR 12.3). Metastases were also more likely with high native tumor density, and bigger size in CT. The cut-off values for tumor size and native density calculated from receiver operating characteristic (ROC) curves were 37mm and 24, respectively. Conclusions Risk of malignancy of adrenal mass in a patient with a history of cancer is high, regardless of hormonal status. Surgical treatment should be considered in all patients with indeterminate adrenal mass and no sign of disseminated cancer.